Novel Zeolite 5Å-Co-Fe based catalytic ozonation process for the efficient degradation of Oxytetracycline in veterinary pharmaceutical wastewater - Amir Ikhlaq; Asma Naeem; Osama Shaheen Rizvi; Asia Akram; Abdul Mannan Zafar; Fei Qi; Ashraf Aly Hassan (Cleaner Water)
Public health and the aquatic environment face significant threats from pollution originating from pharmaceutical wastewater (PhWW) containing stubborn antibiotics. Conventional treatment methods fail to fully eradicate these antibiotics and other contaminants such as COD and BOD5 due to the complex organic compound mixtures present in PhWW. Additionally, PhWW exhibits low biodegradability and high toxicity, mainly due to the persistence of antibiotics. This pressing issue has prompted the scientific community to seek more effective and cost-efficient treatment solutions for detoxifying PhWW. Hence, this study explores the catalytic efficiency of zeolite 5 Å (Z5Å) coated with cobalt and iron (Z5Å-Co-Fe) for the abatement of one of the most persistent organic pollutants oxytetracycline (OTC) as a target pollutant. The synthesized catalyst is assessed using various analytical techniques such as FTIR, SEM, and EDX analysis. Results show that the heterogeneous catalytic ozonation using cobalt and iron-loaded zeolite (Z5Å-Co-Fe/O3) achieves OTC removal rates of 8%, 67%, and 95% through adsorption, ozonation (O3), and Z5Å-Co-Fe/O3 processes, respectively, at pH 6, 1.6 mg/min of O3 flow and 15 min of treatment time. Moreover, the Z5Å-Co-Fe/O3 process demonstrates higher cost-effectiveness compared to other methods, and electrical energy per order (EEO) of 1.47 USD and 1.62 kWh per cubic meter of PhWW respectively. Additionally, it enhances the biodegradability of PhWW from 0.30 to 0.51, making it more suitable for further secondary treatment. Furthermore, Z5Å-Co-Fe/O3 treated PhWW meets National Environmental Quality Standards (NEQS) and holds promise as a pretreatment option for industrial-scale conventional treatment systems. Therefore, it is concluded that the Z5Å-Co-Fe/O3 process was found to be highly efficient for the degradation of OTC in real PhWW matrix and it may help to achieve UN sustainable development goals (SDGs)